Science Literacy and Healthy Living as Determinants of Family Health within the Household Ecology Framework - Ichwan; Mudayat (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines how science literacy and healthy living behaviors jointly shape family health within a household ecology framework. Using a non‐experimental, cross-sectional design, we surveyed 40 mothers from an urban area in western Indonesia. Validated questionnaires (CVI = 0.86; Cronbach’s α ≥ 0.70) measured science literacy, healthy living, and family health. Data were analyzed with Pearson’s correlations and multiple linear regression after meeting parametric assumptions (Shapiro–Wilk p > 0.05; VIF = 1.54; Durbin–Watson = 1.85; no heteroscedasticity). Correlations were positive and significant: science literacy with family health (r = 0.65, p < 0.01), healthy living with family health (r = 0.70, p < 0.01), and science literacy with healthy living (r = 0.58, p < 0.01). The regression model was significant, F(2,37) = 18.45, p < 0.001, explaining 50% of the variance in family health (R² = 0.50). Both predictors contributed uniquely (β_science literacy = 0.35, p = 0.007; β_healthy living = 0.45, p = 0.001), with healthy living showing the stronger effect. Findings underscore that strengthening science literacy is necessary but insufficient unless translated into day-to-day healthy practices. We recommend community-based programs that couple non-formal science education with practice-oriented training (nutrition, sanitation, household hygiene). Future studies should employ larger, longitudinal samples and incorporate socio-economic and environmental covariates.